2004
DOI: 10.1097/01.opx.0000145032.79975.58
|View full text |Cite
|
Sign up to set email alerts
|

Critique of Claims of Improved Visual Acuity after Hypnotic Suggestion

Abstract: Psychological approaches to improving vision present an enticing alternative to invasive procedures and corrective lenses; hypnotic suggestion is one such technique. During the past 60 years, multiple studies have documented improvements in the vision of myopic individuals after hypnotic interventions. Given the increasing interest in behavioral and alternative approaches, we have reviewed the pertinent studies to evaluate their validity. We delineate various shortcomings in these reports, including potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…The findings show that suggestion and expectation can have beneficial effects in a number of clinical conditions , including in common dermatological conditions such as warts and chronic musculoskeletal pain syndromes . Such therapeutic suggestions can help control harmful habits, improve symptoms and provide both immediate and long‐term relief .…”
Section: Discussionmentioning
confidence: 91%
“…The findings show that suggestion and expectation can have beneficial effects in a number of clinical conditions , including in common dermatological conditions such as warts and chronic musculoskeletal pain syndromes . Such therapeutic suggestions can help control harmful habits, improve symptoms and provide both immediate and long‐term relief .…”
Section: Discussionmentioning
confidence: 91%
“…Other studies reported no improvement in vision or auditory thresholds after hypnotic suggestion (18). A 2004 review article summarizes the results of suggestion and hypnosis studies as failing to demonstrate significant improvements in vision or hearing (12). The average visual acuity improvement measured here was over ten-fold, significantly higher than in suggestion or hypnosis studies (Figure 3).…”
Section: Of 14mentioning
confidence: 88%
“…Our study follows Matthews in focusing on PIP, but diverges by isolating two conditions, auditory and visual impairments, that are relatively less sensitive to, although not unaffected by, psychosomatic factors (11)(12). Indeed, researchers have investigated effects of suggestion and hypnosis on vision and hearing and claimed significant effects (13)(14)(15).…”
Section: Of 14mentioning
confidence: 99%
“…Studies have demonstrated that color perception in the brain can be altered by imagery and suggestion in highly hypnotizable subjects [ 5 ]. Other visual changes reported to be inducible by hypnotic suggestion include development of color blindness, tunnel vision, and visual hallucinations [ 6 - 10 ]. Further, it is thought that hypnosis can improve a subject's subjective feeling of visual acuity by improving other cognitive functions such as memory, attention and perceptual learning [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other visual changes reported to be inducible by hypnotic suggestion include development of color blindness, tunnel vision, and visual hallucinations [ 6 - 10 ]. Further, it is thought that hypnosis can improve a subject's subjective feeling of visual acuity by improving other cognitive functions such as memory, attention and perceptual learning [ 10 ]. Thus, the blue-tinted vision experienced by the individuals in this report may be the result of an hypnosis-induced primary change in cognitive processing.…”
Section: Discussionmentioning
confidence: 99%